Answer:
4
Explanation:
When M varies inversely P squared rhen this is represented as
![M=\frac {k}{P^(2)}](https://img.qammunity.org/2021/formulas/mathematics/high-school/s830cblrit1faqf6gol21qaxwveq81on44.png)
Here, k is a constant of proportionality
Now when M is 9 and P is 2, P squared will be 4. Now substituting the value of P squared and M into the equation we can find the xonstant of proportionality as
K=9*4=36
Now that we have k, when P is 3 then we substitute the value of P as 3 and k as 36 into the first equation hence
![M=\frac {36}{3^(2)}=4](https://img.qammunity.org/2021/formulas/mathematics/high-school/9ukptz1z6tmsypbshy0ig3ef30oc2biqo1.png)
Therefore, M=4